Micro, small, and medium-sized enterprises (MSMEs) during the post-pandemic economic recovery period: digitalization, literation, innovation, and its impact on financial performance - Riska Nur Rosyidiana; I. Made Narsa (Cogent Business & Management, 2024)
This study explores the impact of digitalization, literation, and innovation on the financial performance of Micro, Small, and Medium-Sized Enterprises (MSMEs) in Bojonegoro, East Java, Indonesia. Using a sample of 35 business owners, the research employs partial least squares structural equations modelling. The findings reveal a positive and significant relationship between innovation and MSMEs' financial performance, emphasizing the crucial role of innovative practices. Additionally, business owners' literacy levels positively influence innovation. Although digitalization shows a positive impact on innovation and financial performance, the lack of statistical significance calls for nuanced exploration. The study contributes to understanding the complex dynamics within MSMEs post-pandemic, emphasizing the importance of literation and innovation. The research offers practical insights for MSME owners on enhancing financial literacy and fostering an innovative culture within their businesses. Policymakers were also encouraged to allocate resources to facilitate financial training for business owners. Urban areas might employ varying pandemic response strategies depending on their economic circumstances, resulting in differences in interaction variables. Future studies should extend these findings to diverse urban settings to broaden our understanding of literation, innovation, and digitalization's impact on MSME performance.
Keywords: 650; Digitalization; literation; innovation; financial performance; MSMEs